A Descriptive Study on Ethical HR Policies and Practices - Singhal, Harsh (Journal of Advanced Research in HR and Organizational Management, 2022)
Both in the professional world and the academic world, there is a rising interest in modern day business ethics. However, ethical violations continue to occur in the course of business operations, prompting academics and professionals to reevaluate the current state of affairs and devise innovative new approaches to the problem of effectively managing ethics in business organizations. In light of this, although attempts to market ethics are primarily directed on utilizing and developing clear, documented formal mechanisms, the literature argues that alternative tools are equally important and required to accomplish this goal. Due to the significant impact that HRM ethics and practices are believed to have on staff employees, there has been a recent surge in interest in the study of the role that Human Resource Management (henceforth, HRM) plays in promoting ethical behavior in the workplace. In the present paper, we will attempt to provide a comprehensive examination of the role that HRM plays in generating an ethical workplace for the organization.